ý nghĩa chính trị-xã hội của hoạt động khuyến nông Việt Nam hiện nay - Phan, Thanh Khôi (2011)
Tác giả: Phan Thanh Khôi, PGS,TS; Nguyễn Trần Thành, TS; Nguyễn Hoàng Cầm, ThS; Bùi Thị Minh, ThS; và những người khác -- Từ khóa: Khuyến nông